The Implementation Of The Exponential Smoothing Method In Forecasting The Number Of Students At Smk Negeri 3 Bengkulu - Fezi Fadwa Rendika; Liza Yulianti; Jhoanne Fredricka (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
The admission of new students is a routine activity every Academic Year carried out at schools. SMK Negeri 3 Bengkulu City is one of the State Vocational Schools in Bengkulu City which every Academic Year accepts new students. Based on data obtained from the 2011/2012 Academic Year to the 2021/2022, it shows that the level of the number of students sometimes decreases and also increases. This fluctuating pattern of student numbers is a problem faced by SMK Negeri 3 Bengkulu City in determining strategic steps and policies from schools in dealing with PPDB (New Student Admission) in every academic year. The application for forecasting the number of students at SMK Negeri 3 Bengkulu City is an application that can help schools find out how many students there will be in the coming school year based on the results of the analysis conducted from the previous trend data. Forecasting analysis is carried out through Exponential Smoothing Method approach. The results of the tests carried out obtained forecasting results in 2022/2023 academic year as many as 474 students.